2021
DOI: 10.3390/s21051705
|View full text |Cite
|
Sign up to set email alerts
|

Matheuristics for Multi-UAV Routing and Recharge Station Location for Complete Area Coverage

Abstract: This paper presents matheuristics for routing a heterogeneous group of capacitated unmanned air vehicles (UAVs) for complete coverage of ground areas, considering simultaneous minimization of the coverage time and locating the minimal number of refueling stations. Whereas coverage path planning (CPP) is widely studied in the literature, previous works did not combine heterogeneous vehicle performance and complete area coverage constraints to optimize UAV tours by considering both objectives. As this problem ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Drones will, therefore, be able to land at the stations as needed and recharge their batteries without having to return to the base. Finally, using panels is yet another suggestion [33]. The drone will have to carry more weight, which will make flying more challenging, but there is also a sustainable energy source.…”
Section: Limitationsmentioning
confidence: 99%
“…Drones will, therefore, be able to land at the stations as needed and recharge their batteries without having to return to the base. Finally, using panels is yet another suggestion [33]. The drone will have to carry more weight, which will make flying more challenging, but there is also a sustainable energy source.…”
Section: Limitationsmentioning
confidence: 99%
“…It is easy to write a program implementation in practical applications and we can obtain better planning results when combined with the planning algorithm. In the field of robot path planning [ 38 , 39 ], the grid method has been widely regarded by researchers as a typical environment modeling method. With the continuous complexity of environmental information and the continuous improvement of robot autonomy, the grid method is still being used.…”
Section: Path Planningmentioning
confidence: 99%
“…Nevertheless, several existing solutions have tried utilizing SDN or a multi-objective routing for ground vehicles [ 10 , 11 , 12 ]. Moreover, routing in UAVs which considers metrics such as charging stations, VANET supporting networks, and trajectory-based systems has also been proposed [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. An exhaustive review of existing schemes identified that a routing scheme should not consider a single objective while disregarding its byproduct’s impact.…”
Section: Introductionmentioning
confidence: 99%